Reestructuración técnico–administrativa de la empresa Baker Hughes de Colombia-oficina de Bogotá (2018)
The present work of degree that develops next, is a technical administrative restructuration of the company Baker Hughes of Colombia, dedicated to the provision of services of exploration, drilling, exploitation, stimulation and artificial lift for oil and gas wells, the office It is located in the city of Bogotá and from there manages operations throughout Colombia. The purpose of carrying out this project is to make proposals for improvement, both the technical and administrative part of the current processes that are handled in the billing area in order to improve cash flow and reduce payment times. the clients. The restructuring is done with a diagnosis of the current situation of the organization. Based on an analysis of the sector using tools such as PESTAL (political, economic, social, technological, environmental, legal analysis), the MEFE (external factors evaluation matrix) and an internal analysis based on the SWOT matrix (weaknesses) , opportunities, strengths, threats), the MEFI (matrix of evaluation of internal factors) and the self-diagnosis tool of the Chamber of Commerce of Bogotá, which allow detecting the weaknesses present in the productive and administrative areas of the company, achieving actions and strategies for improvement.